Fecal microbiota profiles of growing pigs and their relation to growth performance - König, Emilia; Beasley, Shea; Heponiemi, Paulina; Kivinen, Sanni; Räkköläinen, Jaakko; Salminen, Seppo; Collado, Maria Carmen; Borman, Tuomas; Lahti, Leo; Piirainen, Virpi; Valros, Anna; Heinonen, Mari (Public Library of Science (PLoS), 2025)
The early gut microbiota composition is fundamentally important for piglet health, affecting long-term microbiome development and immunity. In this study, the gut microbiota of postparturient dams was compared with that of their offspring in three Finnish pig farms at three growth phases. The differences in fecal microbiota of three study development groups (Good, Poorly, and PrematureDeath) were analyzed at birth (initial exposure phase), weaning (transitional phase), and before slaughter (stable phase). Dam Lactobacillaceae abundance was lower than in piglets at birth. Limosilactobacillus reuteri and Lactobacillus amylovorus were dominantly expressed in dams and their offspring. Altogether 17 piglets (68%) were identified with Lactobacillaceae at the initial exposure phase, divided unevenly among the development groups: 85% of Good, 37.5% of Poorly, and 75% of PrematureDeath pigs. The development group Good was identified with the highest microbial diversity, whereas the development group PrematureDeath had the lowest diversity. After weaning, the abundance and versatility of Lactobacillaceae in piglets diminished, shifting towards the microbiome of the dam. In conclusion, the fecal microbiota of pigs tends to develop towards a similar alpha and beta diversity despite development group and rearing environment.